Effect of Piper cubeba total extract and isolated lignans on head and neck cancer cell lines and normal fibroblasts - Gusson-Zanetoni, Juliana Prado [UNESP]; da Silva, Julliene Stephanie Guaraldi Monteiro [UNESP]; Picão, Thais Bravo [UNESP]; Cardin, Laila Toniol [UNESP]; Prates, Janesly [UNESP]; Sousa, Stefanie Oliveira [UNESP]; Henrique, Tiago; Oliani, Sonia Maria [UNESP]; Tajara, Eloiza Helena; e Silva, Marcio Luis Andrade; Cunha, Nayanne Larissa; da Silva Gomes, Ana Carolina [UNESP]; et al. (Elsevier, 2022)
The objective of the present study was to evaluate the action of the crude hydroalcoholic extract of Piper cubeba fruits and isolated lignans (cubebin, dihydrocubebin, ethylcubebin, hinokinin and methylcubebin) on head and neck cancer cells. We evaluated the influence of the Piper cubeba extract and isolated lignans (10, 50 e 100 μg/mL) for 4, 24, 48 and 72 h, in the larynx (Hep-2) and oral (SCC-25) squamous cell carcinoma cells and normal fibroblasts, on morphology, cell proliferation and migration, cytotoxicity, genotoxicity and gene and protein expression (PTGS2, PTGER3, PTGER4, MMP2, MMP9). The results showed that the P. cubeba extract and different lignans do not alter the cellular morphology, but decrease cell proliferation and migration, have low cytotoxic and genotoxic effects, probably due to the alteration of the expression of genes and proteins involved with inflammatory process. From these data, we can conclude that the lignans cubebin and methylcubebin had a greater effect on head and neck cancer cells in the antiproliferative, antimigratory and genotoxic action, and could be the target of the development of new therapies including possible new drugs as a therapeutic resource for the treatment of head and neck cancer due to its immense range of biological properties.
Keywords: Anti-inflammatory agents; Bioactive compounds; Phytotherapy